2006
DOI: 10.1111/j.1365-2745.2006.01081.x
|View full text |Cite
|
Sign up to set email alerts
|

Previous land use alters plant allocation and growth in forest herbs

Abstract: Summary1 Former human practices can persistently influence forest ecosystems, particularly by altering the distribution and abundance of vegetation. Previous research has focused on the role of colonization success in governing plant community patterns in abandoned forests, but few studies have explored how changes in the performance of adult plants may contribute to changes in plant populations. 2 We examined patterns of biomass allocation and growth of 12 herbaceous plant species in southern Appalachian fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 55 publications
0
14
3
Order By: Relevance
“…Number of shrub species was higher in the undisturbed stand (18) than in the disturbed stand (16). Nonetheless, the number of herbaceous species remained higher in the disturbed stand (30) than in the undisturbed stand (17). Castanopsis tribuloides was common in both stands, and showed dominance in the undisturbed stand with a density of 90 individuals' ha -1 .…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Number of shrub species was higher in the undisturbed stand (18) than in the disturbed stand (16). Nonetheless, the number of herbaceous species remained higher in the disturbed stand (30) than in the undisturbed stand (17). Castanopsis tribuloides was common in both stands, and showed dominance in the undisturbed stand with a density of 90 individuals' ha -1 .…”
Section: Resultsmentioning
confidence: 82%
“…[62] found that space created by small canopy gaps and environmental historical factors were of comparable importance for controlling herb species composition and distribution while space was of somewhat greater importance for woody plants, and that the past human land use hand a strong impact on species composition on the Barro Colorado Island of Panama. [17] also described that the allocation and growth of herbaceous plants can be altered by previous land use, in their experiment with 12 herbaceous plant species in southern Appalachian forest stands of USA. Thus, the higher total species diversity and lower tree species composition in the disturbed stand may be attributed to the stand characteristic allowing the light-demanding herbaceous species to increase, and in turn suppressing the tree seedlings due to competition with the herbaceous species.…”
Section: Discussionmentioning
confidence: 99%
“…A change in land-use management practices including the conversion from native forests to plantations can alter the rate and type of litter input because of changes in species composition and plant growth rates (Fraterrigo et al 2006;Jandl et al 2007), and subsequently WSOC concentrations (Fig. 3).…”
Section: Discussion Seasonal Patterns Of Wsoc Wson and Wsoc: Wson Ramentioning
confidence: 99%
“…Baeten et al 2009). The number of studies that explore how the (a)biotic legacies of former agricultural practices influence the establishment, performance and persistence of forest herbs is gradually increasing (e.g., Verheyen and Hermy 2004;Vellend 2005;Fraterrigo et al 2006;Flinn 2007;Baeten et al 2009). …”
Section: Vegetative and Regenerative Performancementioning
confidence: 99%